Language-switching and retrieval-based learning: an unfavorable combination - Wußing, Moritz; Grabner, Roland H.; Sommer, Hannah; Saalbach, Henrik (Frontiers in Psychology, 2023)
Language-switching costs arise when learners encode information in one language and subsequently recall that information in a different language. The assumed cognitive mechanism behind these costs is the principle of encoding specifity that implies language-dependent representations of information. The aim of our study was to test this mechanism and to gain insights into the impact of languageswitching on subsequent learning. To this end, we used retrieval-based learning as a carrier-paradigm.In a 2x3-design, 117 participants learned mathematical concepts with a practice-test or a restudy opportunity (within-subjects factor). In addition, the sample was divided into three groups regarding language-switching (between-subjects factor): one group without switching, one switched for the final tests, and one switched between initial learning and subsequent learning.Results show the expected main effects: participants performed better for the items learned via retrieval-based learning (testing-effect) and worse in conditions with language-switching (languageswitching-costs). Most importantly, we were able to find an interaction between learning condition and language-switching: retrieval-based learning suffers particularly from language-switching. Additionally, our results indicate that language switching before subsequent learning seems to be particularly detrimental.These results provide both validation for encoding specificity as mechanism underlying languageswitching costs and new information on the impact of the time of language-switching that can be considered in educational designs such as "Content and Language Integrated Learning".